TARADUF (SINONIM) DALAM PENAFSIRAN AL-QUR’AN - Rafi'atun Najah Qomariah; Radiatun Nazwa (Tarbawi, 2022)
Taraduf is a singular word that refers to something with the same meaning and the same explanation, or something whose words are multiple and contain one meaning. There are pros and cons among the scholars of interpretation regarding the existence of Taraduf in the Quran. This article aims to reveal the opinions of the scholars of Tafsir about Taraduf in the interpretation of the Quran, as well as which words are considered to be Taraduf in the Quran. The research method used by the researcher is literature study. The results show that there are some scholars who reject Taraduf, although some language scholars agree with the existence of Taraduf because for them, Taraduf is one of the peculiarities of the Arabic language. On the other hand, those who declare that there is no Taraduf in the Arabic language state that the words of Taraduf only have similarities in meaning, not the same meaning. Therefore, they try to interpret words that have similar meanings in various ways. Among the examples of words that they consider to be like Taraduf are: khawf and kasyyh, thoriq and Sabil, ja a and ataa, fa’ala and a’mala, and others.